Genotype-phenotype correlations of new causative APC gene mutations in patients with familial adenomatous polyposis. Issue 9 (September 1995) - Bunyan, D J; Shea-Simonds, J; Reck, A C; Finnis, D; Eccles, D M
Abstract : Nine new causative mutations and seven previously characterised mutations of the APC gene of patients with familial adenomatous polyposis (FAP) were analysed for any genotype-phenotype correlations. The only clear genotype-phenotype correlation found was between the position of the mutation site and the presence or absence of congenital hypertrophy of the retinal pigment epithelium (CHRPE). A more distal mutation site was associated with an earlier age of onset of symptoms and a larger number of colonic polyps, but a notable amount of intrafamilial variation was observed.